Family factors choice of college degree or vocation among high school students - Acuña, Pauline Danielle L.; Dela Peña, Angela B.; Reyes, Clarissa F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The implementation of the K-12 Program has been observed to make the decision of students to go for a degree or vocational skills more crucial, as there are two additional years that students have to undergo in high school, and this requires more resource management when it comes to time and money. If the student‟s choice is not well thought of, then he or she may have the tendency to shift to another course. This study seeks to explore and describe the family factors affecting the their decision to go to college, focusing on the background, circumstances, and interaction between parents and children. Thirty-two twelfth grade students were chosen through snowball sampling for in-depth interviews, which allowed for description of the said factors. Data were subjected to coding and contextual analysis where the role of the family in the students' decisions were looked into. Results show that socio-economic status, family values, family circumstances, and parental involvement affected the students' choice of whether to go to college. Moreover, it is also shown that these factors are interrelated and affects each member, and their experiences with their family. With these findings, the study may aid Filipino families in understanding the members' point of views and respective roles in the choice of a college degree.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: College choice -- Philippines -- National Capital Region; High school students -- Philippines -- National Capital Region; Vocational guidance -- Philippines -- National Capital Region